Parent-of-origin effects in SOX2 anophthalmia syndrome. - Osborne, R; Kurinczuk, J; Ragge, N (2011)
PURPOSE: Sex determining region Y (SRY)-box 2 (SOX2) anophthalmia syndrome is an autosomal dominant disorder manifesting as severe developmental eye malformations associated with brain, esophageal, genital, and kidney abnormalities. The syndrome is usually caused by de novo mutations or deletions in the transcription factor SOX2. To investigate any potential parental susceptibility factors, we set out to determine the parent of origin of the mutations or deletions, and following this, to determine if birth order or parental age were significant factors, as well as whether mutation susceptibility was related to any sequence variants in cis with the mutant allele. METHODS: We analyzed 23 cases of de novo disease to determine the parental origin of SOX2 mutations and deletions using informative single nucleotide polymorphisms and a molecular haplotyping approach. We examined parental ages for SOX2 mutation and deletion cases, compared these with the general population, and adjusted for birth order. RESULTS: Although the majority of subjects had mutations or deletions that arose in the paternal germline (5/7 mutation and 5/8 deletion cases), there was no significant paternal bias for new mutations (binomial test, p=0.16) or deletions (binomial test, p=0.22). For both mutation and deletion cases, there was no significant association between any single nucleotide polymorphism allele and the mutant chromosome (p>0.05). Parents of the subjects with mutations were on average older at the birth of the affected child than the general population by 3.8 years (p=0.05) for mothers and 3.3 years (p=0.66) for fathers. Parents of the subjects with deletions were on average younger than the general population by 3.0 years (p=0.17) for mothers and 2.1 years (p=0.19) for fathers. Combining these data, the difference in pattern of parental age between the subjects with deletions and mutations was evident, with a difference of 6.5 years for mothers (p=0.05) and 5.0 years for fathers (p=0.22), with the mothers and fathers of subjects with mutations being older than the mothers and fathers of subjects with deletions. We observed that 14 of the 23 (61%) affected children were the first-born child to their mother, with 10/15 of the mutation cases (66%) and 4/8 deletion cases (50%) being first born. This is in comparison to 35% of births with isolated congenital anomalies overall who are first born (p=0.008). CONCLUSIONS: Sporadic SOX2 mutations and deletions arose in both the male and female germlines. In keeping with several genetic disorders, we found that SOX2 mutations were associated with older parental age and the difference was statistically significant for mothers (p=0.05), whereas, although not statistically significant, SOX2 deletion cases had younger parents. With the current sample size, there was no evidence that sequence variants in cis surrounding SOX2 confer susceptibility to either mutations or deletions.